Breast Cancer Genetics Knowledge and Testing Intentions among Nigerian Professional Women. Issue 4 (19th December 2017) - Ngene, Samuel O.; Adedokun, Babatunde; Adejumo, Prisca; Olopade, Olufunmilayo
Abstract: Genetic testing services for breast cancer are well established in developed countries compared to African populations that bear a disproportionate burden of breast cancer (BC). The objective of this study is to examine the knowledge of professional Nigerian women about BC genetics and their intentions to utilize genetic testing services when it is made available in Nigeria. In this study, 165 lecturers and 189 bankers were recruited and studied using a validated self‐administered questionnaire. The respondents' mean age was 34.9 years (SD = 10.9), 6.5% had family history of BC, and 84.7% had limited knowledge of breast cancer genetics. The proportion of women with genetic testing intentions for breast cancer was 87.3%. Health care access (OR = 2.35, 95% CI, 1.07–5.13), religion (OR = 3.51, 95% CI, 1.03–11.92), and perceived personal risk if a close relative had breast cancer (OR = 2.31, 95% CI, 1.05–5.08) independently predicted testing intentions. The genetic testing intentions for BC were high despite limited knowledge about breast cancer genetics. Promotion of BC genetics education as well as efforts to make BC genetic testing services available in Nigeria at reduced cost remains essential.